Selection of Optimal Conditions for the Separation of Curcuminoids by High-performance Capillary Electrophoresis (HPCE) Using Micellar Electrokinetic Chromatography (MEKC) - D. I. Pisarev; O. O. Novikov; K. S. Nikitin; N. N. Boyko; K. M. Sakanyan; M. Yu. Novikovа (Разработка и регистрация лекарственных средств, 2022)
Introduction. Curcuminoids are natural polyphenolic colorants with a wide spectrum of pharmacological activity. Modern hybrid and classical methods are used for the determination of curcuminoids. However, the problem of the analysis of curcuminoids in the composition of plant and medicinal objects remains relevant. In this work, capillary electrophoresis (HPCE) in the variant of micellar electrokinetic chromatography with diode array detection (MEKC/DAD) was used as such a method.Aim. The purpose of this analysis is the choice of optimal conditions for the separation of curcuminoids using capillary electrophoresis in the form of micellar electrokinetic chromatography.Materials and methods. Separation of curcuminoids was carried out on an Agilent 7100 CE capillary electrophoresis instrument with a diode array detector and an Agilent Chem Station monitoring and data acquisition system. Borate buffer (20 mM, pH 9.3) with the addition of sodium dodecyl sulfate – SDS (30 mM) in ratios of 1 : 1 was used like the electrolyte. The sample was injected hydrodynamically – 50 mbar/3 sec, electrode voltage is +25 kV, quartz capillary – total capillary length/effective capillary length = 30/40 cm, ID = 50 µm, capillary temperature +20 °С. The output of curcuminoids was monitored at the wavelength of the diode-matrix detector – λmax = 425 nm/4 nm, the refereed wavelength is 360 nm/100 nm.Results and discussion. Curcuminoids in a borate buffer solution with the addition of SDS are practically not separated, which is associated with a high activity of the electroosmotic flow, to suppress which 95 % ethyl alcohol was added. In the course of research, it was found that the addition of ethyl alcohol in an amount of 20 % relative to the buffer solution makes it possible to separate the mixture of curcuminoids.Conclusion. Thus, the conditions for the separation of the total curcuminoids by the HPCE method in the variant of micellar electrokinetic chromatography (MEKC) were selected. It has been established that for the separation of curcuminoids by this method, it is necessary to use an electrolyte consisting of a mixture of equal volumes of borate buffer (20 mM) and sodium dodecisulfate (30 mM) and ethyl alcohol in an amount of 20 % of the electrolyte volume. A further increase in the concentration of ethyl alcohol in the electrolyte is unreasonable, since it can adversely affect the stability of micelles.